2012
DOI: 10.1039/c2ob26398j
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 4,6-disubstituted 2-(4-morpholinyl)pyrimidines by cross-coupling reactions using triorganoindium compounds

Abstract: 4,6-Disubstituted-2-(4-morpholinyl)pyrimidines, an important class of bioactive compounds, have been synthesized from 4,6-dichloro-2-(4-morpholinyl)pyrimidine by selective and sequential palladium-catalyzed cross-coupling reactions using triorganoindium reagents. This methodology, being efficient and versatile, allowed the synthesis of a variety of non-symmetrical pyrimidines functionalized at C-4 and C-6 positions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The O6PMe emission displays two clearly distinguishable peaks at 600 and 650 nm and is blueshifted with respect to O5PMe.The broad nature of O5PMe emission beyond 650 nm is suggestive of H-aggregated stacking, improved intermolecular interactions, and the presence of multiple emissive species. 47,48 We also see that while the absorption spectra of O6PMe in solution state (Figure S14) are comparable to its solid-state spectra, the O5PMe solid-state spectra are hypsochromically shifted with respect to its solution-state spectra, further indicative of Haggregated stacking in O5PMe films.…”
Section: ■ Results and Discussionmentioning
confidence: 75%
“…The O6PMe emission displays two clearly distinguishable peaks at 600 and 650 nm and is blueshifted with respect to O5PMe.The broad nature of O5PMe emission beyond 650 nm is suggestive of H-aggregated stacking, improved intermolecular interactions, and the presence of multiple emissive species. 47,48 We also see that while the absorption spectra of O6PMe in solution state (Figure S14) are comparable to its solid-state spectra, the O5PMe solid-state spectra are hypsochromically shifted with respect to its solution-state spectra, further indicative of Haggregated stacking in O5PMe films.…”
Section: ■ Results and Discussionmentioning
confidence: 75%
“…In recent years we have shown that indium organometallics are useful reagents in metal-catalyzed cross-coupling reactions. , Besides their high efficiency, versatility, and selectivity in cross-coupling reactions, triorganoindium reagents (R 3 In) are particularly effective for the synthesis of functionalized heterocyclic compounds, and they exhibit high selectivity in coupling reactions with 3,4-dihalomaleimides, 2,5-dibromothiophenes, and 4,6-dichloropyrimidines . As a continuation of our studies into the application of R 3 In in organic synthesis, we report herein an efficient approach to trisubstituted imidazoles by selective and sequential palladium-catalyzed cross-coupling reactions of triorganoindium reagents with 2,4,5-trihaloimidazoles and the application of this approach to the synthesis of neurodazine and analogues.…”
Section: Introductionmentioning
confidence: 79%
“…Triorganoindium compounds were prepared according to previously published methods by treatment of the corresponding organolithium reagents (3 equiv., ∼0.5 M in dry THF) with a solution of InCl 3 (1.1 equiv., ∼0.05 M in dry THF) at −78 or −20 °C and warming to room temperature.…”
Section: Experimental Sectionmentioning
confidence: 99%
“…dibrominated pyridine, 117 . Triarylindium reagents were also used to synthesize C4 → C6 diaryl pyrimidines, 122 via Pd­(PPh 3 ) 4 -catalyzed sequential arylation of 121 . One-pot arylation provided an unsymmetrical diaryl product in yields that were comparable with that of product formed in the stepwise route, 122a .…”
Section: Sequential C-arylation Of 6-membered Heteroarenesmentioning
confidence: 99%